Nickel Oxide Nanowires Growth by VLS Technique for Gas Sensing Application. (2015) - Kaur, Navpreet; Comini, Elisabetta; Poli, Nicola; Zappa, Dario; Sberveglieri, Giorgio
Abstract: In this work, nickel oxide (NiO) nanowires have been synthesized on alumina substrate by vapor-liquid-solid (VLS) technique and were tested for alcohol sensing. RF magnetron sputtered gold particles were used as catalyst for the growth of NiO nanowires. Nanowire surface morphology was analyzed by using scanning electron microscopy (FE-SEM). Afterwards, a set of conductromertric sensing devices were prepared and mounted on TO packages using electro-soldered gold wires. The response of prepared sensors towards different gases such as acetone and ethanol was measured. The dynamic sensing phenomena and the calibration curves of NiO nanowire sensors exposed towards these gases were also studied in detail. The optimal working temperature of the sensors were found to be 500 °C for both the gases.